(untitled) (Ameghiniana, 2013)
New studies carried out at northem Tontal Range, demonstrated the development of the Portezuelo Tontal Formation towards the north, between Carmen Alto Mine and the San Juan River. The turbiditic sedimentary facies are similar to those of the quebrada del Telegrafo strato-type. The following graptolites were recognized Didymograptus sp., Dicellograptus cf. D. intortus, Dicranograptus sp., Diplograptus sp. and Glyptograptus sp. This fauna characterizes the upper Ordovician (late Llandeilo-Caradoc).